Microwave oscillator – the orotron with the DC magnetic nonuniformity - Odarenko, E. N.; Shmat'ko, A. (SPIE, 1993)
The effect of the profiled profiled focusing field on the operation of the the orotron is studied. The two-dimensional model of the beam-wave interaction is described. The decrease of the starting current and efficiency enhancement are possible for chosen theoretical model.
Keywords: orotron; profiled focusing field; two-dimensional model; nonlinear theory